A Ratio-Defined NVTIA CoQ10–BioPerine®–Vitamin E System for Improved Oral Delivery and Myocardial Redox Support - Yassine, Jabar; Semenza, Gregg L.; Monroe, Ava (International Journal of Public Health and Medical Research, 2026)
Background: Cardiovascular disease remains the leading cause of death worldwide, and mitochondrial redox imbalance is an important component of myocardial dysfunction. Coenzyme Q10 (CoQ10) is mechanistically relevant to cardiac bioenergetics and antioxidant defense, but its clinical translation is constrained by poor oral bioavailability. Objective: We evaluated a ratio-defined NVTIA ternary system composed of CoQ10, BioPerine® (standardized piperine), and vitamin E, while placing its preclinical performance in the context of published formulation, pharmacokinetic, and cardiovascular outcome data. Methods: We examined three dosage-form embodiments disclosed for the ternary system and compared them with a binary CoQ10–piperine reference. We then summarized peer-reviewed studies on CoQ10 absorption, piperine-mediated exposure enhancement, formulation engineering, and heart-failure outcomes to assess translational plausibility. Results: In the available rat dataset, the ternary system increased relative plasma total CoQ10 to 1.19–1.38-fold and myocardial reduced CoQ10 to 1.79–2.13-fold versus the binary comparator. The 100:15:1 soft-capsule embodiment showed the highest myocardial enrichment. Published human data indicate that piperine coadministration can increase CoQ10 plasma exposure by about 30% after 21 days, and recent formulation studies confirm that lipid-based encapsulation materially improves CoQ10 bioaccessibility and cellular uptake. Meta-analytic and randomized clinical evidence further supports the clinical relevance of CoQ10 in chronic heart failure. Conclusion: The NVTIA ternary system is supported by a coherent mechanistic framework in which formulation engineering, piperine-assisted absorption, and vitamin E–linked redox support may jointly improve delivery of reduced CoQ10 to cardiac tissue. The preclinical signal is strong enough to justify prospective human validation, but the exact ternary ratio still requires registered clinical testing.